Scrotoschisis: An extremely rare congenital anomaly - Ram M Shukla; Kartik C Mandal; Dipankar Roy; Mahadev P Patra; Biswanath Mukhopadhyay (Wolters Kluwer Medknow Publications, 2012)
A rare case of unilateral scrotoschisis in a full term infant delivered by Caesarean section is reported.